ANALISIS POTENSI PAJAK PARKIR DALAM MENINGKATKAN PENERIMAAN PAJAK DAERAH DI KABUPETEN KARAWANG - Agus Subagiyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Regional Tax according to Law No.34 of 2000 as amended the latest by Law number 28 of 2009 that Regional Tax is the contribution of taxpayers to regions that are owed by an individual or a body that is compelling based on the law, with no reward directly and used for regional needs for the greatest prosperity of the people. The basis for tax collection is carried out by the regional Government in accordance with law number 32 of 2004 as ammanded by Law No. 12 of 2008 concerning regional autonomy wich states that the government and the people in the regionsare allowed to take care or their own households responsibly. Karawang regency is famous for its parking tax revenue target and realization of parking tax which continues to increase every year.increasing the target every year within the last three years 2015-2017 is based on the achievement of the parking tax realization received. When viewed in terms of the determination of the largest target number, it accurred in 2017, which amounted ti IDR 4,000,000,000 from the previous year 2016, which was IDR 1,750,000,000 which increased by IDR 2,250,000,000. If seen from the realization, the biggest income occured in 2017 with the total realization of Rp.3,063,776,838 with a percentage of 76.59% but was not achieved when viewed against the target of the determination. In terms of achieving the target, the biggest percentage occurred in 2016 with a realization of Rp.1,950,622,021 with a percentage of 111.46%. with the failure to achieve the target in 2017, there are obstacles that arise during the implementation process in the field